DIPLOMASI KEBUDAYAAN ITALIA DI INDONESIA MELALUI LEMBAGA BUDAYA ITALIA (ISTITUTO ITALIANO DI CULTURA) - Rosa Mika Susan; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Italy is aware of the potential of its country in the culture so that it uses it as a tool of cultural diplomacy to countries that have diplomatic relations with Italy, one of which is Indonesia. Diplomacy Italian culture through Italian culture institutions (instituto Italiano di cultura) in Indonesia aims to introduce the arts, language and culture of the country to the Indonesian people in order to achieve their national interests. This study uses a constructivist perspective, cultural diplomacy theory, the concept of soft power and the level of analysis of the nation state. The research method used is descriptive qualitative research by collecting data from the IIC official website, the Italian Ministry of Foreign Affairs website, interviews with IIC parties via gmail, and whatsapp, as well as scientific journals, books and other websites. Italian cultural diplomacy towards Indonesia through IIC is going well with on going activities such as learning Italian, providing scholarship information from the Italian government, seminars, visits school and organizing cultural activities in the form of film screenings, introducing Italian cuisine that is maintained existence. Keywords: Cultural Diplomacy, Istituto Italiano Di Cultura (IIC), Italy, Indonesia.